EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING PADA MATERI BARISAN DAN DERET ARITMATIKA - Manuk, Herman Kaiser; Jamiah, Yulis; Yani T, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to know and to describe the effectiveness of Creative problem solving learning  model  on rank and series of arithmetic material in grade X of SMK Budi Luhur Sintang. The researcher using pre-experimental method in the form of quantitative research. The participant of this research was 31 students of class X AKL SMK Budi Luhur Sintang. The implementation of teachers class management is 3,21  in the first meeting and declined to 3,08  in the second meeting. The student activity is 66% in the first meeting and  improved to 68% on the second meeting. The result showed that the students learning mastery is achieved classically 78,28%. On the other hand, students responds towards Creative Problem Solving learning model In a good category  From  the  collected  data,  it  can  be  concluded  that  Creative Problem Solving learning model  technique to be applied on teaching rank and series of arithmetic material in grade X of SMK Budi Luhur Sintang.Keywords : Creative Problem Solving, Effectiveness, Rank and Series of Arithmetic